Transport progress as a pledge of national economy development - Myamlin, S. V. (Science and Transport Progress, 2021)
Purpose. To determine the influence of transport branch development through the state order implementation for rolling stock and infrastructure projects in the basic economic branches. Methodology. On the basis of situation and content analyses the impact of particular science branches development on improvement of transport modes is analyzed. The role of engineering approach for both the problem solving of the stagnant technologies negotiation and new designs creation as well as solving the economic problems at a national level is observed. Findings. The impact of transport development on the national economy improvement is analyzed; during this the active role of scientific and technical progress of transport branch is investigated. The efficient means to increase the effectiveness of national economy are analyzed; one of these means is the state order for production of the basic industry branches. All the components of the production process while launching the innovational rolling stock manufacture, including the results of scientific, project and production organizations researches are taken into account. Practical value. It is proved that, provision of the state order for domestic enterprise production is the main way of national economics strengthening and the basic direction of the life quality improvement in the country. The state order for transport branch production will solve a number of social problems of regional and state level.